Examining Nurse Empathy for Infant Procedural Pain: Testing a New Video Measure - Margot Latimer; Philip Jackson; Celeste Johnston; Jocelyn Vine (Pain Research and Management)
BACKGROUND: Research reporting effective pain care strategies exists, yet it is not translated to care. Little is known about how repeated pain exposure has affected nurses’ ability to be empathetic and use their knowledge to provide evidence-based care. Concerns have been raised regarding the validity of self-report empathy instruments; therefore, a novel video program was developed for testing. It was hypothesized that those who viewed infants in painful and nonpainful states would have a measureable empathy (pain rating) response correlating to the level of pain expressed by the infants.